2016
DOI: 10.5539/jas.v8n11p1
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Value of Crisphead ‘Iceberg’ and Romaine Lettuces (Lactuca sativa L.)

Abstract: <p>Lettuce (<em>Lactuca sativa</em> L.) is one of the most popular vegetables worldwide, but is often viewed as low in nutritional value. However, lettuce contains health-promoting nutrients and biosynthesis of such phytochemicals varies depending on cultivar, leaf color and growing conditions. Studies of such parameters on the nutritional value have not been conclusive because the lettuce samples were collected from heterogeneous growing conditions and/or various developmental stages. In our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 10 publications
3
32
2
Order By: Relevance
“…In the current study, total phenolic concentration was significantly higher in red leaf 'Scarlet' than green leaf with purple veins 'RR' and green leaf 'DBC' kale, but there was no significant difference between 'DBC' and 'RR' (Table 2). Studies have reported higher total phenolic content in red compared to green cultivars of lettuce (Lactuca sativa L.) (Liu et al, 2007;Llorach, Martínez-Sánchez, Tomás-Barberán, Gil, & Ferreres, 2008;Kim et al, 2016). Regardless of leaf color, total phenolics in all three kale cultivars were higher in BL2 and adult stages (128.3-250.5 mg GAE/100 g FW) than early stages (MG1, MG2 and BL1, 54.6-170.1.0 mg GAE/100 g FW) ( Table 2).…”
Section: Total Phenolics and Anthocyaninsmentioning
confidence: 91%
“…In the current study, total phenolic concentration was significantly higher in red leaf 'Scarlet' than green leaf with purple veins 'RR' and green leaf 'DBC' kale, but there was no significant difference between 'DBC' and 'RR' (Table 2). Studies have reported higher total phenolic content in red compared to green cultivars of lettuce (Lactuca sativa L.) (Liu et al, 2007;Llorach, Martínez-Sánchez, Tomás-Barberán, Gil, & Ferreres, 2008;Kim et al, 2016). Regardless of leaf color, total phenolics in all three kale cultivars were higher in BL2 and adult stages (128.3-250.5 mg GAE/100 g FW) than early stages (MG1, MG2 and BL1, 54.6-170.1.0 mg GAE/100 g FW) ( Table 2).…”
Section: Total Phenolics and Anthocyaninsmentioning
confidence: 91%
“…Lettuce contains a variety of minerals and beneficial to human health, such as Fe, Zn, Ca, P, Mg, Mn, K, etc. Lettuce has been eaten by more and more people as a healthy food in recent years in China [1][2] . Lettuce can be divided into six types, namely crisphead lettuce, butterhead lettuce, romaine or cos lettuce, leaf or cutting lettuce, steam or stalk lettuce and latin lettuce, according to the shape, size, texture, head formation and stem type of lettuce leaves [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al . () reported that crisphead or iceberg lettuce has the lowest nutritional value whereas butterhead and romaine lettuce were the highest in terms of their nutritional value among the lettuce types in the United States.…”
Section: Introductionmentioning
confidence: 99%